Lean enterprise - Humble, Jez; Molesky, Joanne; O'Reilly, Barry (O'Reilly, 2014)
How well does your organization respond to changing market conditions, customer needs, and emerging technologies when building software-based products? This practical guide presents Lean and Agile principles and patterns to help you move fast at scale-and demonstrates why and how to apply these methodologies throughout your organization, rather than with just one department or team. Through case studies, you'll learn how successful enterprises have rethought everything from governance and financial management to systems architecture and organizational culture in the pursuit of radically impr. -- Resumé vydavatele
Keywords: softwarové inženýrství; inovace; testování softwaru; software engineering; innovations; software testing; příručky; elektronické knihy; handbooks and manuals; electronic books